Answer:
![√(2a^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kn6rcdlranuiiqjpk2kosnvh11nei6ydod.png)
Explanation:
The distance between two points (x₁ , y₁) and (x₂ , y₂) is d
![d= √((x2-x1)^2+(y2-y1)^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iqwks6sz55fsmrjdg3iz0awxtevjsxe9pd.png)
For the given points (0, a) and (a, 0)
Substitute at the previous equation
![d=√((a-0)^2+(0-a)^2)=√(a^2+a^2)=√(2a^2) =a√(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e92x7n0oqze1wg246mauu2p806dd3jyn39.png)
So, the expression represents the distance between point (0, a) and point (a, 0) on a coordinate grid is StartRoot 2 a squared EndRoot ⇒
![√(2a^2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kn6rcdlranuiiqjpk2kosnvh11nei6ydod.png)